Peningkatan Kompetensi Guru Bahasa Asing dalam Mengimplementasikan Extensive Reading/Tadoku di SMA Nurul Ikhlas - Maulluddul Haq; Ainul Addina; Syafitri Ramadhani; Nur Rosita; Honesty Yonanda Ayudhia; Dian Lestari Despiani; Nadya Bethazel Ariesty; Refy Faustina Khairani (Universitas Negeri Padang, 2026)
The teacher competency-development training on the use of extensive reading/Tadoku has the potential to enhance teachers’ knowledge and motivation in applying this approach to support the improvement of students’ foreign-language literacy. This activity was carried out at SMA Nurul Ikhlas, Tanah Datar Regency, involving 14 foreign-language teachers. It aimed to provide participants with knowledge on how to implement extensive reading in foreign-language instruction, as well as how to utilize available print and digital learning resources. The training employed a method consisting of 70% theoretical exposition and 30% classroom demonstration in a Japanese-language class. Data were collected through four-point Likert-scale questionnaires and open-ended questions, and analyzed using descriptive quantitative methods and qualitative thematic analysis. The results indicate that the majority of participants experienced an increase in knowledge and insight related to the approach and found the materials relevant to the challenges faced in their classrooms. Most participants also reported feeling motivated and capable of applying the approach in their own teaching. It is concluded that the extensive reading/Tadoku training was effective in expanding teachers’ knowledge and understanding, thereby contributing to enhanced teacher competence in achieving foreign-language literacy goals